2015
DOI: 10.35762/aer.2015.37.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Current Situation of Cd Contamination in Agricultural Field in the Mae Sot District, Tak Province, Northwestern Thailand

Abstract: This paper reviews contamination status, sources and remediation of Cd in agricultural land in Mae Sot District, Tak Province, Northwestern Thailand. The Cd contamination becamean environmental issue because mining of a Zn deposit area located uphill of the Mae Tao creekscaused movement of Cd and Zn along the creek to contaminate agricultural soils downstream. Blood Cd levels of residents in this contaminated area were found to exceed the national average of 0.5 μg g-1creatinine. The main route of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In 2004, an estimated 8,350,185.05 acres of rice fields were contaminated with cadmium, impacting 12 villages with a total population of 12,075 [6]. Similar to Cd pollution levels in the Mae Sot region, the International Water Management Institute (IWMI) reported that Cd levels in rice grains were 90% higher than the recommended safety levels [7]; this was in agreement with our findings and other published studies about Cd contamination in an agricultural field in the Mae Sot District, Tak Province, Northwestern Thailand [8,9]. The Cd concentration in unhusked rice (Oryza sativa L.) grains ranged from 0.04 to 1.75 mg Cd/kg, and more than half of the households' rice contained Cd levels higher than the CODEX-mandated critical level of 0.4 mg Cd/kg refined rice [10].…”
Section: Introductionsupporting
confidence: 91%
“…In 2004, an estimated 8,350,185.05 acres of rice fields were contaminated with cadmium, impacting 12 villages with a total population of 12,075 [6]. Similar to Cd pollution levels in the Mae Sot region, the International Water Management Institute (IWMI) reported that Cd levels in rice grains were 90% higher than the recommended safety levels [7]; this was in agreement with our findings and other published studies about Cd contamination in an agricultural field in the Mae Sot District, Tak Province, Northwestern Thailand [8,9]. The Cd concentration in unhusked rice (Oryza sativa L.) grains ranged from 0.04 to 1.75 mg Cd/kg, and more than half of the households' rice contained Cd levels higher than the CODEX-mandated critical level of 0.4 mg Cd/kg refined rice [10].…”
Section: Introductionsupporting
confidence: 91%
“…The phytotoxicity during the time period over 90 days of the experiment shows that have exhibit toxicity symptoms in the treatment process with Pb but without EDTA, with Pb and EDTA 0.01 mM L −1 and treatment of Pb and EDTA 0.02 mM L that, C. esculenta exhibited toxicity in the treatment of Pb and EDTA 0.03 mM L − symptoms included, for example, wilting leaves, curling leaves, yellow color appearing in leaf margins and plants eventually dying (Akkajit, 2015). Moreover, Pb might be able to interfere with and resist the process of photosynthesis by absorbing nutrients into plants.…”
Section: Effects Of Pb and Edta On Esculentamentioning
confidence: 97%
“…Both creeks finally run to the Mei river, the border line of Thailand and Myanmar (Kosolsaksakul et al, 2014). Public Company Limited was the largest Zn mine in Southeast Asia and has been operated in this area for more than 30 years (Akkajit, 2015). The production capacity of Zn was about 110,000 metric tons per year (Akkajit, 2015).…”
Section: Scope Of the Studymentioning
confidence: 99%
“…Public Company Limited was the largest Zn mine in Southeast Asia and has been operated in this area for more than 30 years (Akkajit, 2015). The production capacity of Zn was about 110,000 metric tons per year (Akkajit, 2015). Waste generation from Zn mine, including Cd as a by-product (U.S.EPA, 2000a), and natural soil erosion in potential Zn mineral area were reported to be the significant sources of soil, water and plant contamination in this area (Simmons et al, 2005;DPIM, 2010;Kosolsaksakul et al, 2014;Sriprachote et al, 2014;Akkajit, 2015).…”
Section: Scope Of the Studymentioning
confidence: 99%
See 1 more Smart Citation